2015
DOI: 10.1007/s00423-015-1308-9
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization (TACE) for colorectal liver metastases—current status and critical review

Abstract: There is encouraging data with regard to technical success, safety, and oncologic efficacy of TACE for colorectal liver metastases. The majority of studies are non-randomized single-center series mostly after failure of systemic therapies in the 2nd line and beyond. Emerging techniques including embolization with calibrated microspheres, with or without additional cytotoxic drugs, degradable starch microspheres, and technical innovations, e.g., cone-beam computed tomography (CT) allow a new highly standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 101 publications
0
43
0
7
Order By: Relevance
“…There are three categories of TACE: 1) conventional (cTACE), 2) degradable starch microsphere (DSM‐TACE), and 3) drug eluting bead (DEB‐TACE). In cTACE, cytotoxic chemotherapy is injected into the artery, which is then embolized with permanent agents (for example, polyvinyl alcohol particles) that are often size calibrated to target a specific arterial level . In DSM‐TACE, one or more cytotoxic agents are mixed with DSM‐TACEs, causing a temporary arterial occlusion .…”
Section: Regional Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three categories of TACE: 1) conventional (cTACE), 2) degradable starch microsphere (DSM‐TACE), and 3) drug eluting bead (DEB‐TACE). In cTACE, cytotoxic chemotherapy is injected into the artery, which is then embolized with permanent agents (for example, polyvinyl alcohol particles) that are often size calibrated to target a specific arterial level . In DSM‐TACE, one or more cytotoxic agents are mixed with DSM‐TACEs, causing a temporary arterial occlusion .…”
Section: Regional Therapiesmentioning
confidence: 99%
“…DEB‐TACE combines the two methods: permanent embolic agents are coated with cytotoxic therapies allowing for a controlled release of the drug into the tissues over hours or days. Currently, this is the most standard and accepted of the TACE technologies . DEB‐TACE can be used in patients with adequate liver function in tumors without vascular invasion and has been studied in non‐resectable colorectal liver metastases and as a neo‐adjuvant therapy to downstage patients for surgical resection or ablation with objective response rates of 42% to 78% and progression‐free survival of 11 to 19 months .…”
Section: Regional Therapiesmentioning
confidence: 99%
“…With a focus on technical issues, for thermal ablation, homogeneous ablation zones (considering the desmoplastic growth pattern of ICC) and homogeneous safety margins of at least 1 cm (due to the ill-defined margins of ICC on computed tomography/magnetic resonance imaging/ultrasound) and for different transarterial therapies, optimization of the protocols (e.g. doses and types of chemotherapeutic agents, types and sizes of embolic agents, internal radiation dose, treatment intervals, and response evaluation) are of particular relevance [3,4,6,18]. For the future, complex multimodal concepts are the key to further improve progression-free and overall survival as well as the quality of life in patients with CC in different stages.…”
Section: Discussionmentioning
confidence: 99%
“…Additional publications were identified after crosschecking of the reference lists of the articles extracted by means of primary selection. A description of the different modalities and techniques available for locoregional therapy is not outlined in this overview; however, it can easily be obtained from other publications [1,2,3,4,5,6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…We used degradable starch microsphere (DSM)-TACE with EmboCept® S (450 mg/7.5 mL; PharmaCept, Berlin, Germany) with a particle mean size of 50 µm. These particles are dissolved by human amylase and cause temporary vascular occlusion with a recanalization time of approximately 1 h [13]. No studies have shown if oxaliplatin could be mixed with EmboCept® S and therefore EmboCept® S was injected after the infusion of oxaliplatin.…”
Section: Methodsmentioning
confidence: 99%